Executive Remuneration, Option Incentives--- An Empirical Study in China - LUO, Dan (2006)
Prior executive remuneration researches are mainly concentrated on the risk neutral valuation of stock options; or measuring the sensitivity of the pay for performance relationship based on data collected from US. However, this paper aims to investigate the scheme implementation in the biggest developing country: China. According to the first hand information collected from a survey of executive stock option scheme in Zhongguancun, we are able to depict the general picture of such equity-based incentive scheme implementation in China. Our results suggest that although employees in China have general knowledge of stock option and most companies believe that such option scheme may improve their performance, they are far from mature to implement such scheme successfully. Furthermore, considering the specific situation of China, if a company has determined that the use of options is immediately necessary for the recruitment and retention of employees, the options should be granted in a manner that is in compliance, to the extent determinable, with the current laws and regulations. In addition, we also investigate the factors that might influence the possibilities of a company adopting the scheme based on a logit model. Four variables are found significant related to the decision making: ywby (whether the company think it is necessary), ygrs (the number of employees), zls (number of patent owned) and sfss (listed or not). And the model also lead us to believe that although there are only few companies in China using this scheme currently, most companies are interested in the scheme (97.209%). However, concerning the possibility of companies using stock option in the future, the results deducted from the logit model is kind of confusing but if taking the fast development of Chinese economy also into account, a promising picture is brought forth that as stock markets become more regulated and as companies grow bigger, stock option will certainly be used as an effective incentive mechanism and improve the performance of the companies dramatically.